Bolivia Social Accounting Matrix, 2012 - International Food Policy Research Institute; Inter-American Development Bank; Institute for Advanced Development Studies; Kiel Institute for the World Economy (International Food Policy Research Institute, 2015)
The Bolivia Social Accounting Matrix (SAM), 2012 was built with a focus on analyzing the structure and importance of the agricultural sector and gender differences in the Bolivian economy, and understanding the linkages between agricultural production, factor income distribution, and households' incomes and expenditures. It is the most detailed, openly accessible SAM for Bolivian economy to date. The 2012 Input-Output (I-O) was the main data source used in building the disaggregated activity sector and comm odity accounts of the 2012 Bolivia SAM.